2009
DOI: 10.1063/1.3139069
|View full text |Cite
|
Sign up to set email alerts
|

Highly temperature insensitive, deep-well 4.8 μm emitting quantum cascade semiconductor lasers

Abstract: 4.8   μ m emitting, quantum cascade (QC) lasers that suppress carrier leakage out of their active regions to the continuum have been realized by using deep (in energy) quantum wells in the active regions, tall barriers in and around the active regions, and tapered conduction-band-edge relaxation regions. The characteristic temperature coefficients T0 and T1 for the threshold current density Jth and slope efficiency, respectively, reach values of 238 K over the 20–60 °C temperature range, which means that Jth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 15 publications
1
35
0
1
Order By: Relevance
“…The larger threshold current density compared to the previous structures [2] emitting around 7.1 µm is attributed to increased waveguide losses. The characteristic temperature for the slope efficiency T 1 shows four different values in the temperature range of 78-400 K. Around room temperature T 1 is 108 K. Though the value is lower than that reported for deep-well design QCLs, it is comparable to T 1 of a high efficiency QCL emitting at 4.6 µm [14]. The inset of Fig.…”
Section: R  mentioning
confidence: 72%
“…The larger threshold current density compared to the previous structures [2] emitting around 7.1 µm is attributed to increased waveguide losses. The characteristic temperature for the slope efficiency T 1 shows four different values in the temperature range of 78-400 K. Around room temperature T 1 is 108 K. Though the value is lower than that reported for deep-well design QCLs, it is comparable to T 1 of a high efficiency QCL emitting at 4.6 µm [14]. The inset of Fig.…”
Section: R  mentioning
confidence: 72%
“…Cathabard et al [13] showed that InAs/AlSb QCLs emitting at wavelengths as short as 2.63-2.65 mm can be optimized to weaken carrier leakage into the L-valley by reducing coupling between the active InAs quantum wells. In 4.8 mm QCLs Shin et al and Botez et al reduced G-X inter-valley leakage by increasing the depth of the active quantum wells through making the barriers around the active region higher or by pushing the upper mini-band in the relaxation region away from the active region and hence from the X-valley by tapering the conduction band edge of the injector [14,15] and active regions [15]. Such an approach may be relevant to reducing G-L inter-valley carrier leakage in these devices as will be the subject of ongoing studies.…”
Section: G-l Leakmentioning
confidence: 97%
“…As a result, there is strong overlap between wavefunctions corresponding to upper energy levels in the active regions and wavefunctions corresponding to lower levels in the upper G minibands, which in turn leads to severe carrier leakage from the active regions to the continuum [3,4]. The carrier leakage manifests itself, above room temperature, as quite low characteristic temperature values for both the threshold-current density (i.e., T 0 $140 K) [1,2] and the slope efficiency (i.e., T 1 is $ 140 K) [1].…”
Section: Introductionmentioning
confidence: 98%
“…We have developed varying composition QCL structures that employ deep (in energy) wells and tall barriers in the active regions, so-called deep-well QCL structures [3], thus providing much larger energy differential between the upper laser state and the top of the exit barrier than in conventional devices (i.e., $450 meV vs. $ 250 meV), and as a result, suppressing carrier leakage. In addition, the highly strained layers are located only in a portion of each stage (i.e., in the active region), thereby reducing the overall strain within each stage.…”
Section: Introductionmentioning
confidence: 99%